ChemInform Abstract: Catalytic Methylation of Aromatic Amines with Formic Acid as the Unique Carbon and Hydrogen Source. Issue 13 (March 2015) - Savourey, Solene; Lefevre, Guillaume; Berthet, Jean‐Claude; Cantat, Thibault
Abstract The formation of the N—Me group proceeds via a formylation/transfer hydrogenation pathway.